Effects of dietary supplemental antioxidants (selenium and vitamin C), triiodothyronine hormone and iodine on performance, nutrients retention and relative organ weights in broilers exposed to cold conditions (15°C) - Seven, P. Tatli; Dalkilic, B.; Seven, I.; Arslan, O. (Ecole Nationale Veterinaire Toulouse, 2009)
The study was carried out to determine the effects of antioxidants (selenium and vitamin Q, triiodothyronine hormone and iodine supplements on feed intake (171), body weight gain (BWG), feed conversion ratio, mortality, crude nutrients retention and relative organ weights of broilers exposed to cold conditioning (15 degrees C). In this study, 150 broiler chicks, Ross 308, one-day-old, were used. Chicks were randomized into 1 control and 4 treated groups each containing 30 birds and each experimental group comprised 3 replicates of 10 birds. The experimental groups were: group I (control group), any added supplement in their diet, group II received selenium (Se) (1mg/kg) + iodine (1) (2mg/kg) in their diet, group III Se (1mg/kg) + triiodothyronine (T3) hormone (1mg/kg), group IV vitamin C (Vit C) (250 mg/kg) + 1 (2 mg/kg) and group V Vit C (250 mg/kg) + T3 hormone (1 mg/kg). BWG and 171 of groupIV (Vit C+I) in 15-40 d were found significantly better in comparison with the control group. Crude protein retentions of groups II (Se+I), IV (Vit C+I) and V (Vit C+T3) were significantly higher than control group (P<0.05). Relative heart weights were significantly increased by dietary supplementation of Vit C+T3, group V (P<0.05). This effect was connected with dietary T3 supplementation. Relative thyroid weights were significantly higher in control group than in treated groups (P<0.01). According to these results, it could be said that antioxidant dietary supplements have performed constructive effects in cold conditioning. Dietary vitamin C combined to I and T3 was found to be more effective in comparison to dietary Se plus I or T3.
Keywords: Triiodothyronin; selenium; iodine; vitamin C; zootechnical performances; cold condition; broilers